Peningkatan keterampilan menulis tegak bersambung menggunakan metode pembelajaran struktural analitik sintetik peserta didik kelas II sekolah dasar - Soufi Dianimdri; Muhammad Ismail Sriyanto; Hadiyah Hadiyah (Universitas Sebelas Maret, 2019)
Abstract. The aim of this research was to improve the cursive handwriting skills through the use of learning methods Stuctural Analitic Synthetic (SAS). Here the researcher used an action classroom research in two cycles. Technique that choosen for collect data are interview, observation, test, and documentation. The data validity test technique uses data triangulation include sources triangulation, technique triangulation, and content validity . The data analysis technique uses descriptive comparative and analytic comparative technique shown by interactive model learning. The result of this research showed the improvement of value in initial pre-action test score were 50,7 with classical completeness of 12%, and then increased in the first cycle by 68,5 with classical completeness of 40%, and in second cycle it increased highly to 81,79 with classical completeness of 84%. The conclusion that can be obtained based on these data are the use of SAS learning methods can improve the cursive handwriting skills in second grades students of SDN Bumi 1 No.67 Surakarta in academic year 2018/2019. Keywords: Structural Analytic Synthetic (SAS), cursive handwriting skills, Elementary School